When All Is Said and Done: The Aftermath of Welfare “Reform” in the United States - Tourigny, Sylvie C. (Social justice, 2001)
Although the need for a broadened and reformed welfare state is perhaps greater than ever, ideological opposition to the welfare state has never been so great, so well organized, and so powerfully represented. Economic laws do not demand poverty, homelessness, and other forms of inequality, and the failure to prevent the increase of homelessness represents the most careless inattention to the consequences of a smaller middle class, a larger poverty class, and a pervasive abatement of equality.